'Dr Google': trends in online interest in prostate cancer screening, diagnosis and treatment. (11th July 2019) - Rezaee, Michael E.; Goddard, Briana; Sverrisson, Einar F.; Seigne, John D.; Dagrosa, Lawrence M.
Abstract : Objectives: To examine trends in online search behaviours related to prostate cancer on a national and regional scale using a dominant major search engine. Materials and Methods: Google Trends was queried using the terms 'prostate cancer', 'prostate‐specific antigen' (PSA), and 'prostate biopsy' between January 2004 and January 2019. Search volume index (SVI), a measure of relative search volume on Google, was obtained for all terms and examined by region and time period: pre‐US Preventive Services Task Force (USPSTF) Grade D draft recommendation on PSA screening; during the active Grade D recommendation; and after publication of the recent Grade C draft recommendation. Results: Online interest in PSA screening differed by time period ( P < 0.01). The SVI for PSA screening was greater pre‐Grade D draft recommendation (82.7) compared to during the recommendation (74.5), while the SVI for PSA screening was higher post‐Grade C draft recommendation (90.4) compared to both prior time periods. Similar results were observed for prostate biopsy and prostate cancer searches. At the US state level, online interest in prostate cancer was highest in South Carolina (SVI 100) and lowest in Hawaii (SVI 64). For prostate cancer treatment options, online interest in cryotherapy, prostatectomy and prostate cancer surgery overall increased, while searches for active surveillance, external beam radiation, brachytherapy and high‐intensity focused ultrasonography remained stable. Conclusion: Online interest in prostate cancer has changed over time, particularly in accordance with USPSTF screening guidelines. Google Trends may be a useful tool in tracking public interest in prostate cancer screening, diagnosis, and treatment, especially as it relates to major shifts in practice guidelines.